TRADE THROUGH THE DESERT: A LONG-TERM PERSPECTIVE ON GOODS, ANIMALS, AND POLITIES IN THE NEGEV - Rosen,Steven A (Universidad de Tarapacá. Facultad de Ciencias Sociales y Jurídicas. Departamento de Antropología, 2019)
Caravan trade in the Near East, and in the Negev, is the culmination of millennia of cumulative social and technological development, essentially an expression of complex economy societies with large-scale markets. The origins of caravan trade systems are to be sought in the specifics of their historical circumstances. For example, Nabatean trade developed in the wake of the rise of market demand in the Classical Mediterranean for such goods as spices, incense, etc., and in the specific geographic context of the Negev as land bridge between the Tropics and the Mediterranean. A longer-term view of desert trade traces the precursors of caravans back to earlier systems of exchange between the desert and settled zones. Such a perspective offers a cumulative view of the contexts and development of such trade systems, beginning as early as the Epipaleolithic, and evolving through the Neolithic, Chalcolithic, Bronze and Iron Ages. In this sense, the historically specific trade systems of such groups as the Nabateans fit into a larger set of longer term patterns, ever more complex in terms of diversity of goods, their social functions, distance of travel, technologies of transport, bulk of goods, social and economic frameworks for the trade, and infrastructure investment.